Safety and immunogenicity of two formulations of rotavirus vaccine in Vietnamese infants. Issue 32 (22nd July 2021) - Thiem, V.D.; Anh, D.D.; Ha, V.H.; Hien, N.D.; Huong, N.T.; Nga, N.T.; Thang, T.C.; McNeal, M.M.; Meyer, N.; Pham, H.L.; Huong, N.M.; Gompana, G.; et al.
Highlights: Phase 3 study compared two rotavirus vaccines manufactured by POLYVAC in Vietnam. ROTAVIN-M1® (licensed) is stored at −20 °C and ROTAVIN is stored at 2–8 °C. Study compared the safety and immunogenicity of two doses of the two formulations. The results indicate immunological non-inferiority of ROTAVIN to ROTAVIN-M1. The two formulations were determined to have a similar safety profile. Abstract: Background and aims: ROTAVIN-M1® (licensed, frozen vaccine) and ROTAVIN (second-generation, liquid candidate vaccine) are two rotavirus vaccine formulations developed from a live attenuated G1P8 (KH0118) strain by Center for Research and Production of Vaccines and Biologicals (POLYVAC), Vietnam. This study compared the safety and immunogenicity of these two formulations. Methods: A Phase 3, randomized, partially double-blinded, active-controlled study was conducted in healthy infants aged 60–91 days in Vietnam. Infants received two doses of ROTAVIN or ROTAVIN-M1 in a ratio of 2:1 with an interval of 8 weeks. Solicited reactions were collected for 7 days after each vaccination. Blood samples were collected pre-vaccination and 4 weeks after the second vaccination in a subset of infants. Non-inferiority criteria required that the lower bound of 95% confidence intervals (CIs) of the post-vaccination anti-rotavirus IgA GMC (Geometric Mean Concentration) ratio of ROTAVIN/ROTAVIN-M1 should be >0.5. A co-primary objective was to compare the safety of the two vaccines in terms of solicited reactions. Results: A total of 825 infants were enrolled. The post-vaccination GMC was 48.25 (95% CI: 40.59, 57.37) in the ROTAVIN group and 35.04 (95% CI: 27.34, 44.91) in the ROTAVIN-M1 group with an IgA GMC ratio of 1.38 (95% CI: 1.02, 1.86) thus meeting the pre-set criteria for non-inferiority. A total of 605 solicited reactions were reported in 297 (36.0%) participants with 35.4% in the ROTAVIN group and 37.2% in the ROTAVIN-M1 group. There were no cases of intussusception or death reported in the study. Conclusions: Based on the data generated, it can be concluded that ROTAVIN is immunologically non-inferior and has similar safety profile to ROTAVIN-M1 when administered to infants in a two-dose schedule. Therefore, it can be considered as a more suitable option for programmatic use to prevent rotavirus diarrhoea in Vietnam and the Mekong region. Trial registration number: ClinicalTrials.gov identifier: NCT03703336, October 11, 2018.